Analisis Biaya Produksi Dan Hasil Pendapatan Usahatani Cabai Merah (Capsicum Annum L.) - MZ, Ali Mawali; Sibuea, Mhd Buhari (Universitas Medan Area, 2024)
The demand for red chilies shows indications that it continues to increase along with the increase in population and increasing national economic stability. The reason for conducting this research was to determine the amount of production costs incurred and the income from red chili farming. The research location was carried out on the Bukit Kor land, Terengganu, Malaysia, determining the research location using the Purposive Sampling method. Using census data collection techniques, researchers use all members of the population. Factors that influence the growth of chilies are sunlight, humidity, rainfall and soil type. The number of samples collected in this research was 50 respondents as a population of farmers who raise red chilies in that location. The data obtained was processed tabulatedly, then continued for analysis using the formula π = TR – TC. The results of the analysis of red chili farming on the Bukit Kor land with a land area of 1 Ha showed that the total production was 48 tons/MT, and to production costs were IDR 86,070,250/Mt. The results of this research stated that red chili farming on the Bukit Kor land, Terengganu obtained a final income profit of IDR 1,505,706,980/Mt.